Villa-Lobos’s Eighth String Quartet (1944): neoclassicism and invention (Orfeu, 2017)
The formal structure in the four movements of Villa-Lobos’s Eighth StringQuartet (1944) reveals his concern to reinterpret classical form (sonata form, andante, minuet/scherzo, and sonata rondo) according to the post-tonal harmonyhe developed during the 1920s. This study investigates the correlations between harmony and form, interpreting some analogies apparently made by Villa-Lobosto emulate points of formal articulation as seen in classical music. The employmentof some peculiar chord structure, with recurrence of interval symmetry instead ofthe traditional tonality, indicated that an analytical approach based on set theorywould be more adequate to this analysis.
Keywords: String quartet; Neoclassicism; Formal analysis; Symmetry; Villa-Lobos (1887-1959)